Effect of Deformation and Heat Treatment on the Structure, the Mechanical Properties, and the Fracture Characteristics of an Ultrafine-Grained Zr-1Nb Alloy; Russian Metallurgy (Metally); Vol. 2017, iss. 4 - Grabovskaya G. P. Galina Petrovna; Stepanova E. N. Ekaterina Nikolaevna; Mishin I. P. Ivan Petrovich; Vinokurov V. A. Vladimir Alekseevich (2017, 2017)
Title screen